Modulação temporal de efeitos em matéria tributária pelo STF - Molinari, Flávio Miranda (2020)
This project aims to analyze the legal institute of modulation of effects in tax matters based on the jurisprudence of the Federal Supreme Court in the control of constitutionality diffuse and concentrated since its entry into force through the Laws n º S. 9.868/99 and 9.882/99 to the present, from the tabulation and analysis of the decisions given in this selected interval, in order to verify whether there is a decision-making standard on the interpretation of the meaning and scope of the expressions "legal certainty" and "exceptional social interest" contained in the authorizing norms of modulation in the aforementioned legislations, as well as the application of these in cases of change of jurisprudential understanding, as overruling cases, which turned out to be a criterion of legal norms for temporal modulation of effects from the Code of Civil Procedure of 2015. This analysis presupposed a theoretical tool to assist in understanding the modulation of effects inserted in the legal system, from the legal positivism, in the strand of the authors Hans Kelsen and H.L.A. Hart, passing through the characteristics of contemporary constitutionalism, as well as evaluating the characteristics of effectiveness of constitutional norms and the role of constitutional jurisdiction in the Brazilian context. The analysis concluded that it is possible to affirm the existence of patterns about temporal modulation of effects in tax matters by the STF in some specific situations, such as cases of change of jurisprudence and requirement of proof of severe injury to the social environment, as well as it is possible to identify characteristics of cases in which the factual situation leads to patterns that require the modulation of effects, as the case of the change of jurisprudence in tax matters, and which reject the Modulation, such as cases in which there is no empirically proven existence of irreversible social impairment. However, it is not possible to find a decision standard that is used in the STF to define "legal certainty" and "exceptional Social interest". In practice, decisions use these expressions followed by hypothetical examples that confirm the need for their guarantee, as if that were enough to guarantee the validity of the manipulation of decisions declaring unconstitutionality.